2019
DOI: 10.1016/s1474-4422(18)30454-x
|View full text |Cite|
|
Sign up to set email alerts
|

Global, regional, and national burden of epilepsy, 1990–2016: a systematic analysis for the Global Burden of Disease Study 2016

Abstract: SummaryBackgroundSeizures and their consequences contribute to the burden of epilepsy because they can cause health loss (premature mortality and residual disability). Data on the burden of epilepsy are needed for health-care planning and resource allocation. The aim of this study was to quantify health loss due to epilepsy by age, sex, year, and location using data from the Global Burden of Diseases, Injuries, and Risk Factors Study.MethodsWe assessed the burden of epilepsy in 195 countries and territories fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
275
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 644 publications
(279 citation statements)
references
References 38 publications
3
275
0
1
Order By: Relevance
“…1 Therefore, research toward new means to suppress seizures is very important. More than one-third of patients continue to have seizures despite best available treatment with antiepileptic drugs (AEDs) and many patients have unacceptable drug-related side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, research toward new means to suppress seizures is very important. More than one-third of patients continue to have seizures despite best available treatment with antiepileptic drugs (AEDs) and many patients have unacceptable drug-related side effects.…”
Section: Introductionmentioning
confidence: 99%
“…More than one-third of patients continue to have seizures despite best available treatment with antiepileptic drugs (AEDs) and many patients have unacceptable drug-related side effects. 1 Therefore, research toward new means to suppress seizures is very important.…”
Section: Introductionmentioning
confidence: 99%
“…We hope to help disseminate Web-based digital pathology tools into regions of the world where genetic testing or advanced neuropathology expertise is not a common or even available standard. 49,50 In conclusion, our study demonstrated the successful use of deep learning in the diagnosis of histomorphologically difficult-to-classify MCD entities. Morphological features learned by the system and relevant for the classification of FCD IIb and cortical tuber were then integrated into a fourtiered classification score successfully validated through a Web-based application, thereby boosting the yield of diagnostic accuracy in a nonexpert group to expert level performance.…”
Section: Limitations and Potential Solutions Moving Into The Futurementioning
confidence: 60%
“…We can imagine facilitating elaborated classification and visualization methods as teaching tools for medical students and pathology trainees. We hope to help disseminate Web‐based digital pathology tools into regions of the world where genetic testing or advanced neuropathology expertise is not a common or even available standard …”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a chronic neurological disease of brain dysfunction that has received widespread attention in society [1,2]. Recent studies have shown that a total of 45.9 million people suffer from epilepsy in the world, which is one of the important causes of disability and death in the population [3].…”
Section: Introductionmentioning
confidence: 99%